Phenotypic spectrum of the first Belgian MYBPC3 founder: a large multi-exon deletion with a varying phenotype - Boen, Hanne M.; Alaerts, Maaike; Van Laer, Lut; Saenen, Johan B.; Goovaerts, Inge; Bastianen, Jarl; Koopman, Pieter; Vanduynhoven, Philippe; De Vuyst, Elke; Rosseel, Michael; Heidbuchel, Hein; Van Craenenbroeck, Emeline M.; et al. (Frontiers in Genetics, 2024)
Variants in the MYBPC3 gene are a frequent cause of hypertrophic cardiomyopathy (HCM) but display a large phenotypic heterogeneity. Founder mutations are often believed to be more benign as they prevailed despite potential negative selection pressure. Methods: Probands with HCM caused by a pathogenic deletion of exon 23-26 of MYBPC3 were identified through genetic screening using a gene panel encompassing 59 genes associated with cardiomyopathies in a single genetic centre in Belgium. Cascade screening of first-degree relatives was performed, and genotype positive relatives were further phenotyped. Cardiac outcomes included death, heart transplantation, life-threatening arrhythmia, heart failure hospitalization or septal reduction therapy. Haplotype analysis, using microsatellite markers surrounding MYBPC3, was performed in all index patients to identify a common haplotype. Results: We identified 24 probands with HCM harbouring the MYBPC3 exon 23-26 deletion. A common haplotype of 1.19 Mb was identified in all 24 probands, with 19 of the probands sharing a 13.8 Mb haplotype. The founder event was estimated to have happened five generations, or 175-200 years ago, around the year 1830 in central Flanders.Through cascade screening, 59 first-degree relatives were genetically tested, of whom 37 (62.7%) were genotype positive (G+) and 22 (37.3%) genotype negative (G-). They were on average 38 ± 19 years old at time of genetic testing. Subsequent clinical assessment revealed a HCM phenotype in 19 (51.4%) G+ relatives. Probands were older (63 ± 10 vs. 42 ± 21 years; p<0.001) and had more severe phenotypes than G+ family members, presenting with more symptoms (50% vs 13.5%; p=0.002), arrhythmia (41.7% vs 12.9%, p=0.014), more overt hypertrophy and left ventricular outflow tract obstruction (43.5% vs 3.0%; p<0.001). Male G+ relatives more often had a HCM phenotype (78.6% vs 34.8%; p=0.010) and were more severely affected than females. Conclusion: A Belgian founder variant, an exon 23-26 deletion in MYBPC3, was identified in 24 probands and 37 family members. The variant is characterized by a high penetrance of 78.6% at the age of 50 years but has variable phenotypic expression. Adverse outcomes were observed in 20.3% patients during follow-up.